2020
DOI: 10.1182/blood.2019003867
|View full text |Cite
|
Sign up to set email alerts
|

GPS2 promotes erythroid differentiation by control of the stability of EKLF protein

Abstract: Erythropoiesis is a complex multistage process that involves differentiation of early erythroid progenitors to enucleated mature red blood cells, in which lineage-specific transcription factors play essential roles. Erythroid Krüppel-like factor (EKLF/KLF1) is a pleiotropic erythroid transcription factor that is required for the proper maturation of the erythroid cells, whose expression and activation are tightly controlled in a temporal and differentiation stage-specific manner. Here, we uncover a novel role … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…As a critical subunit of the NCOR/SMRT complex, GPS2 is mainly located in the nucleus. 17 Recent studies have shown that GPS2 plays important roles in the cytoplasm, including promoting erythroid differentiation by controlling the stability of the EKLF protein 34 and regulating multiple stages of B cell development by inhibiting Ubc13‐mediated ubiquitination. 35 However, few studies have explored the relationship between the expression of GPS2 and the progression and prognosis of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…As a critical subunit of the NCOR/SMRT complex, GPS2 is mainly located in the nucleus. 17 Recent studies have shown that GPS2 plays important roles in the cytoplasm, including promoting erythroid differentiation by controlling the stability of the EKLF protein 34 and regulating multiple stages of B cell development by inhibiting Ubc13‐mediated ubiquitination. 35 However, few studies have explored the relationship between the expression of GPS2 and the progression and prognosis of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Giemsa stain assay was performed as previously described ( Ma et al, 2020 ). Briefly, the cells were collected by centrifugation and resuspended in PBS at different times of differentiation.…”
Section: Methodsmentioning
confidence: 99%
“…Key molecular participants in these networks encompass iron, regulators of iron metabolism like transferrin receptors-1 and -2, as well as early acting hematopoietic growth factors including stem cell factor and interleukin-3. Additionally, classical hormones like thyroid hormones, androgens, corticosteroids, activin/inhibin, and others are integral components [30][31][32][33][34].…”
Section: Regulation Of Steady-state Erythropoiesismentioning
confidence: 99%